The effect of exercise protocol on the development of exercise induced hypoxemia in triathletes - Laursen, P. B.; Rhodes, E. C.; Langill, R. H.; Taunton, J. E.; McKenzie, D. C. (2001)
The purpose of this study was to determine the effect of an exercise protocol (cycle ergometry versus treadmill running) on the attainment of exercise induced arterial hypoxemia (EIH). Thirteen triathletes (training equally in both cycling and running) performed aerobic capacity (VO2max) tests both on a running treadmill and a cycle ergometer. At maximal exercise, no significant differences (p > 0.05) existed between the run and the cycle respectively in the following variables: VO2 = 4.77± 0.15 vs. 4.58 ± 0.14 L× min-1, SaO2 = 92.7 ± 0.6 vs. 93.4 ± 0.7%, VE = 163 ± 5 vs 170 ± 7 L× min-1, Tvent = 3.47 ± 0.42 vs. 3.21 ± 0.37 L× min-1, and VE/VCO2/ = 30.9 ± 0.8 vs. 32.4 ± 1.0. Furthermore, there was no relationship found between SaO2 and VE/VCO2/ when cycle/run data were combined (r = 0.049, p > 0.05), nor was there a relationship between differences in SaO2 and VE across the exercise modes. These findings differ from recent research comparing the development of EIH between protocols. The differences are likely the result of the specific exercise mode training of this subject group creating similar cardiovascular and respiratory responses during maximal exercise. However, these data are in accordance with previous research suggesting the development of a decrease in SaO2 does not mainly occur via a relative hypoventilation, but likely through other mechanisms such as ventilation perfusion inequality or diffusion limitations.